2016
DOI: 10.1111/wrr.12402
|View full text |Cite
|
Sign up to set email alerts
|

Collagen structural alterations contribute to stiffening of tissue after split‐thickness skin grafting

Abstract: The gold standard treatment for full thickness injuries of the skin is autologous split-thickness skin grafting. This involves harvesting the epidermis and superficial dermis from healthy skin and transplanting it onto the prepared wound bed. The donor site regenerates spontaneously, but the appendages and cellular components from the dermal layer are excluded from the graft. As a result, the new tissue is inferior; the healed graft site is dry/itchy, has decreased elasticity, increased fragility, and altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…A study has shown that, in the process of skin graft, an imbalance between collagen synthesis and its cross-linkage and/or the lack of dermal appendages make it relatively less elastic and vulnerable to immobility (contracture) [2]. The progression of healing following skin grafting/skin injury is similar [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study has shown that, in the process of skin graft, an imbalance between collagen synthesis and its cross-linkage and/or the lack of dermal appendages make it relatively less elastic and vulnerable to immobility (contracture) [2]. The progression of healing following skin grafting/skin injury is similar [9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to age factor, chronic exposure of the skin to UV rays [18] or treatment with laser light [19] also affect the collagen content of scar. Therefore, the wounds would heal more slowly and the skin will be more vulnerable to environmental stressors [2]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular note is that the proportion of collagen fibres that are aligned increases in keloid and surgical scar tissue [ 104 , 105 , 106 ]. The collagen fibre bundles in scarred skin after grafting have been shown to be straighter and thinner [ 85 ]. These factors appear to contribute to the decrease in the tensile strength of the scar compared with normal skin [ 85 , 107 ].…”
Section: Alterations In Fibrillar Collagens In the Disease Statementioning
confidence: 99%
“…We report here the first use of the birefringence mode of the LC-PolScope for quantitatively imaging fibrillar collagen in tissues, and comparing it against SHG microscopy. Previous studies [32,33] have used the LC-PolScope as a tool for looking at directionality of collagen fibers and alignment in collagen gels but not for quantitating collagen organization in pathology samples. This study proposes that the LC-PolScope could be a powerful tool for histopathology by measuring changes in collagen organization.…”
Section: Introductionmentioning
confidence: 99%